Application of Designing Economic Mechanisms to Power Market - Part 2 Characteristic Analysis of Generation Side Power Market - ZHU Yonggang; XIE Qingyang; YING Liming (Institute of Advanced Engineering and Science, 2013)
The incentive power market may lead to a high information cost if it is not informationally efficient. The paper analyzes the characteristic of the generation side power market mechanism model based on the designing economic mechanisms theory by the three GENCOs (Generation Companies) case. The result of analysis is that the mechanism model has four main features: the informationally efficient which means that the mechanism meets requirements of the observational efficiency, the communication efficiency and the low complexity of computing; the incentive compatibility which indicates that the resource allocation of the power market is Pareto Optimality and the social benefit achieves the maximization when GENCOs also achieve profit maximization; the decentralized decision which refers to preserving the privacy information of GENCOs; encouragement of competition which suggests that the mechanism encourages GENCOs to compete with each other healthily. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2370